DESIGN OF CHAIRMAN ELECTION SYSTEM OF OSIS PRIVATE VOCATIONAL SCHOOL PELITA PEMATANGSIANTAR USING E-VOTING - Victor M. Pakpahan; Tommy Gultom (Sean Institute, 2020)
One of the mandatory activities that are routinely held annually by all high schools throughout Indonesia is the election of the OSIS Chair. In the OSIS Chair Election, the OSIS Chair Election committee usually carries out their respective ways and ideas. However, the election of the student council president using the conventional method usually takes a long time and costs a lot of money. In addition, in the election of the OSIS chairman, the conventional method produces paper waste resulting from the production of ballot papers. Therefore, the purpose of this study is the need for an E-voting application for the Election of the Student Council Chair to overcome the problems caused by the conventional election of the Student Council Chair. By using the E-voting application for the Election of the OSIS Chair, users can freely choose the candidate they want to be elected and apply election principles. The OSIS Chair Election Committee can also easily list all elements participating in the election. The result of this research is that there is an application design for the election of the OSIS Chair using E-voting that uses a MySQL database.